The Use of Word Walls Technique to Improve Students’ Eleventh Grade Writing Ability in Descriptive Text - Riswanto Riswanto; Reko Serasi; Sekar Mayang Verliana (Yayasan Karinosseff Muda Indonesia, 2023)
This study aims to determine the differences in cognitive learning outcomes (in the form of pre-test and post-test scores) of students in class X IPA 1 as a control class and class XI IPA 4 as experimental class at SMA N 1 Bengkulu Tengah, by providing treatment using the Word Walls. This type of research is Quasi Experiment. The population is eleventh grade students of SMA N 1 Bengkulu Tengah with 368 students. From this population, 37 students were taken as samples. Each class is 35 students XI IPA 1 and 35 students XI MIPA 4. Research data were collected through writing tests and documentation. The results showed a significant change in the experimental class with an average value of 71.63 while in the control class an average value of 58,37. The post-test results show that the Word Walls strategy can improve students' writing skills. Thus, the Word Walls strategy can be one of effective strategy to increase students‟ writing ability.